Treatment of Prion Disease: Is it possible? A Review - Devaraj, Navin Kumar (Jordan Medical Journal, 2025)
Just when scientists believed they had a stronghold on human micro-organisms, up come a new group of disease called prion disease. This new category of disease is fatal in both infected humans and animals. First detected as scrapie in sheep and goats in as early as 1730s, it has evolved and possibly mutated to now infect humans who consume meats of sheep, goats and cows, among others. This review article attempts to look at existing and potential treatment for this currently incurable disease. It is hoped that this article will give scientists hope to continue their tireless struggle to find a cure for this illness.